Notice of Retraction Study on the Impact of Grid Harmonic Voltage on SVG and the Suppression - Renjie Hu; Guiping Yi; Yan Xu (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
Notice of Retraction-----------------------------------------------------------------------After careful and considered review of the content of this paper by a duly constituted expert committee, this paper has been found to be in violation of IAES's Publication Principles.We hereby retract the content of this paper. Reasonable effort should be made to remove all past references to this paper.The presenting author of this paper has the option to appeal this decision by contacting ijeei.iaes@gmail.com.-----------------------------------------------------------------------Industrial Static Var Generator (SVG) is typically applied at or near the load center to mitigate voltage fluctuation, flicker, phase unbalance, non-sine distortion or other load-related disturbance. Special attention is paid to the influence of grid harmonic on SVG current, the harmonic grid voltage causes not only the AC current distortion but also the DC voltage fluctuation. The harmonic voltage decomposition algorithm and DC voltage control are also introduced. All these analyses can guide the practical applications. The simulation results verify the feasibility and effectiveness of the present control strategy and analyses.